MODERN APPROACHES TO STUDYING ALISHER NAVOI'S GHAZALS - Kamolova Khurshidakhon Nurmukhammadovna (International Journal of Literature and Language Studies, 2026)
This scholarly article explores the comprehensive paradigm shift in the methodology of studying and teaching the ghazals of the eminent 15th-century poet and philosopher, Alisher Navoi. Modern approaches have increasingly transcended traditional philological constraints and rote learning, favoring an interdisciplinary synthesis of digital humanities, interactive pedagogy, sophisticated literary theory, and dynamic translation methodologies. By leveraging high-resolution manuscript digitization, linguistic data modeling, Problem-Based Learning (PBL), visual structural mapping, and Sufi symbolic deconstruction, contemporary researchers and educators successfully bridge the temporal and cultural divide between the Timurid Renaissance and the 21st-century global academic arena. The article demonstrates how these integrated frameworks not only preserve Navoi’s profound poetic and linguistic heritage but also ensure its continuous relevance, critical accessibility, and integration into the global literary canon.